Condition of Coral Reefs in the Waters of Kalasey Satu Village, Minahasa Regency, North Sulawesi - Pitoy, Israel; Rembet, Unstain N. W. J.; Rondonuwu, Ari B.; Wantasen, Adnan S.; Kambey, Alex D.; Manu, Gaspar; Tombokan, John L. (Sam Ratulangi University, 2023)
The waters of Kalasey I Village have various resources and environmental services that are the potential to be utilized sustainably, such as tourism. The development activities in the tourism sector look so fast in this area with the establishment of several tourism infrastructures, such as diving centers, cottages, resorts,s and restaurants. These activities are thought to be able to affect the coral reef ecosystem. This study aims to determine the coral reef conditions, especially the reef flat, based on the percent cover of the live corals. Data collection was carried out at a depth of 3 meters with 3 replications using an Underwater Photo Transect (UPT) technique. Data obtained were analyzed using Coral Point Count with excel extension (CPCe) software. Based on the percent cover of live corals, the condition of coral reefs in the Kalasey 1 village waters was classified as poor with a coral cover percentage of 2.93%. Keywords: Tourism development, Underwater Photo Transect (UPT), percent cover, coral point count (CPCe) Abstrak Perairan di Desa Kalasey I memiliki berbagai sumberdaya serta jasa lingkungan yang berpotensi untuk dimanfaatkan secara berkesinambungan seperti potensi pariwisata. Kegiatan pembangunan di sektor pariwisata terlihat begitu pesat di wilayah ini dengan berdirinya sejumlah infrastruktur pariwisata seperti diving center, cottage, resort dan rumah makan, dimana aktivitas tersebut diduga dapat mempengaruhi ekosistem terumbu karang. Penelitian ini bertujuan untuk mengetahui kondisi terumbu karang, khususnya rataan terumbu (reef flat), berdasarkan persentase tutupan karang di perairan Desa Kalasey I Kecamatan Mandolang Kabupaten Minahasa. Pengambilan data dilakukan pada kedalaman 3 meter dengan 3 ulangan, menggunakan teknik Underwater Photo Transect (UPT) dan data yang diperoleh dianalisis menggunakan software Coral Point Count with excel extension (CPCe). Diperoleh hasil kondisi terumbu karang tergolong dalam kategori miskin dengan persentase tutupan karang sebesar 2.93 %. Kata kunci: Pembangunan pariwiata, Underwater Photo Transect (UPT), persen tutupan, coral point count (CPCe)